Consumer behavior-focused training in retailing education: Too much of a good thing? - Hidajat Hendarsjah; Haryanto Haryanto (Jurnal Pendidikan Vokasi, 2021)
Consumer behavior training extensively delivered in the tertiary vocational school of business had been expected to equip students with deep knowledge in marketing and sales. This was true when students were dealing with general business environments, but it was dubious when it was implemented in a certain field of business, such as retail business. Retail business, predictably, had a unique characteristic in its business decisions. Students in the Marketing Program of a tertiary vocational school in their final year were the object of the study. Employing the non-parametric tools to assess student knowledge in consumer behavior and its association with retailing decisions mastery, it was found that student mastery in consumer behavior did not associate with better knowledge in other five retail business decisions (determining the composition of goods, spotting locations, pricing, profit strategy, and store management). The article also provided a brief explanation that specific knowledge in consumer behavior did not always in line with the required knowledge in the retail business. It was also suggested that to elaborate whether one particular knowledge of business practices had a valuable feature was, first, by determining its overall decisions relating to it.  Then, the second, establishing a series of analyses to assess whether the decisions have any relations with the college's courses or training of a field of study.  Comprehension of the process might help the vocational school to equip students with the right required knowledge and skills for a certain field of business.